Caracterização microestrutural da zona termicamente afetada do passe de acabamento de junta de aço 9%Ni soldada pelo processo GMAW por meio de simulações física e computacional - Rios, Mara Cardoso Gonçalves (2019)
The 9% Ni steel was developed in the 40’s to meet the demands of high strength and great fracture toughness at cryogenic temperatures. Recently, this steel has been used in oil platforms for CO2 reinjection where contaminants such as H2S can be found. The effect of this environment on corrosion resistance and mechanical properties on quenched and tempered 9% Ni steel is still not well known, especially when the welding process is involved, where the microstructure in the region close to the weld can be completely changed. In this work a 9% Ni welded steel tube was used and the heat affected zone of the cap pass of the 9% Ni Q & T steel was investigated. Different welding thermal cycles were simulated computationally and physically reproduced. Eight peaks temperatures were chosen in order to characterize the main regions of the thermally affected zone. The microstructure of the reproduced specimens was analyzed by optical, scanning and transmission electron microscopy, X-ray diffraction, dilatometry and magnetic saturation. Image analysis was performed to evaluate the distribution, volumetric fraction and mean size of the austenite, with direct correlation with the results of x-ray diffraction. It was observed that the percentage of austenite present in the heat affected zone is a function of the peak temperature. In addition, martensite and coalesced bainite were shown as the main constituents of the heat affected zone.